Import competition and domestic transport costs - Andrea Caragliu; Michiel Gerritse (Tinbergen Institute, 2022)
With China's 2001 WTO accession, trade costs between the US and China fell sharply, but the transport costs of Chinese imports within the US remained sizable. We argue that domestic transport costs shield local labor markets from globalization. Using a shift-share design for industry-level Chinese imports across 42 ports of entry, we show that US job losses from competing imports occurred near the ports where they arrived. Once accounting for domestic transport costs, import competition affects coastal areas more than inland areas; shows larger impacts in housing markets and indirectly affected jobs; and explains voting, mortality and family formation
Keywords: E24; F14; F16; R23; J23; J31; L60; O47; R12; 330; import competition; local labor markets; trade infrastructure; China syndrome; transport costs